Упростите выражения1x-2x+3+x-3x+221 – x + 4×2 – 8×3 + 2×3упростите выражения1x-2x+3+x-3x+221 – x + 4×2 – 8×3 + 2×3упростите выражения1x-2x+3+x-3x+221

1 Январь 0001



упростите выражения1)(x-2)(x+3)+(x-3)(x+2)2)(1 – x + 4×2 – 8×3) + (2×3упростите выражения1)(x-2)(x+3)+(x-3)(x+2)2)(1 – x + 4×2 – 8×3) + (2×3упростите выражения

1)(x-2)(x+3)+(x-3)(x+2)

2)
(1 – x + 4×2 – 8×3) + (2×3 + x2 – 6x – 3) – (5×3 + 8×2) 

3)
(0,5a – 0,6b + 5,5) – (–0,5a + 0,4b) + (1,3b – 4,5)

4)
(–2×2 + x + 1) – (x2 – x + 7) – (4×2 + 2x + 8) 

5)
(3a2 – a + 2) + (– 3a2 + 3a – 1) – (a2 – 1)

6)
2a–3b+c–(4a+7b+c + 3)



7)
 2xy – y2 + (y2 – xy) – (x2 + xy)

8)(y-1)(y+2)+(y+1)(y-2)

9)(a+1)(a+2)+(a+3)(a+4)

10)(c-1)(c-2)+(c-3)(c-4)

  • 1)x^2+3x-2x-6+x^2+2x-3x-6=2x^2-12
    2)1-x+4x^2-8x^3+2x^3+x^2-6x-3-5x^3-8x^2=-11x^3-3x^2-7x-2
    3)0,5a-0,6b+5,5+0,5a-0,4b+1,3b-4,5=a+0,3b+1
    4)-2x^2+x+1-x^2+x-7-4x^2-2x-8=-7x^2-14
    5)3a^2-a+2-3a^2+3a-1-a^2+1=-a^2+2a+2
    6)2a-3b+c-4a-7b-c-3=-2a-10b-3
    7)2xy-y^2+y^2-xy-x^2-xy=-x^2
    8)y^2+2y-y-2+y^2-2y+y-2=2y^2-4
    9)a^2+2a+a+2+a^2+4a+3a+12=2a^2+10a+14
    10)c^2-2c-c+2+c^2-4c-3c+12=2c^2-10c+14








Алгебра

Комментарии закрыты.